Direct access to trifluoromethylated α-hydroxyketones from silver-catalyzed hydroacyloxylation of trifluoromethyl propynols with acids. (9th January 2023) - Song, Xiao-Fang; Zhang, Li-Jing; Zhang, Xing-Guo; Tu, Hai-Yong
Abstract: A general and efficient method for the synthesis of trifluoromethylated α-acyloxyketones has been developed via silver-catalyzed hydroacyloxylation of trifluoromethyl propynols with a variety of acids. The obtained α-acyloxyketones can be easily hydrolyzed under acidic conditions to afford the corresponding trifluoromethylated α-hydroxyketones, and undergoes various further transformations. Graphical abstract: Image 1